Cooling Enhancement of a Photovoltaic Panel Through Ferrofluid Stimulation Using a Magnetic-Wind Turbine - N. Heidari; M. Rahimi; N. Azimi (Iranian Journal of Chemical Engineering)
Wind energy is used to rotate a magnetic turbine in order to remove heat from the surface of a photovoltaic (PV) panel. A three-bladed turbine, which rotates with wind energy, has rotational motion underneath the studied PV panel in order to move Magnetic Nano-Particles (MNPs). In addition, effects of the magnetic field strength (B=450-830 mT), rotational velocity of the magnetic turbine (ω), and the concentration of MNPs (ϕ) on the heat removal from the PV panel area were investigated. Results showed that heat removal from PV panel was intensified by motion of pinned MNPs in the ferrofluid via the exerted external force of magnetic field. Concurrent application of available magnetic field along with ferrofluid led to 7.6-24 % temperature reduction for a PV panel. Furthermore, the produced electrical energy of the PV panel was augmented between 2.55-3.13 W depending on ϕ, ω, and B. Moreover, the impact of ω on cooling performance was also investigated, and a significant enhancement to generated power was observed. Eventually, the maximum amount of the produced power (3.13 W), maximum power enhancement percentage (32.63 %), and thermal efficiency (24 %) were achieved for B=830 mT, ω=50 cycles/min, and ϕ=0.05 (w/v).